Evaluation of a Culturally Tailored Educational Video Intervention to Promote Bike Helmet Safety for Urban Children: A Pilot Study. Issue 6 (November 2020) - Ryan, Leticia Manning; Solomon, Barry S.; Ziegfeld, Susan; Gielen, Andrea; Malloy, Lauren; Foster, Daniel; McDonald, Eileen
Bicycle-related falls are a significant cause of mortality and morbidity. Use of bicycle helmets substantially reduces risk of severe traumatic brain injury but compliance with this safety practice is particularly low in urban children. Given the lack of educational interventions for urban youth, our research team created a youth-informed, culturally relevant educational video on bike helmet safety, which was informed by focus groups with Baltimore City youth. This video, You Make the Call, linked the concept of use of cases to protect phones to use of helmets to protect heads and can be viewed athttp://bit.ly/2Kr7UCN . The impact of the video as part of an intervention (coupled with a free helmet, fit instructions, and a parent guidance document) was tested with 20 parent–child dyads. The majority (80%) of youth (mean age 9.9 ± 1.8 years) reported not owning or wearing a helmet. At 1-month follow-up (n = 12, 60% response rate), helmet use was higher in the five youth reporting bike-riding after the intervention; 100% "always" used helmets compared to 0% preintervention. There were increases in youth reporting that parents required helmet use (35% pre vs. 67% post) and that is was possible to fall when bike-riding (60% pre vs. 92% post). These pilot results support the use of this video and educational intervention along with further evaluation in a larger sample size. This youth-informed and culturally tailored approach could be explored as a strategy to address other pediatric injury topics.